Surveillance of adverse events in the treatment of drug-resistant tuberculosis: A global feasibility study - Akkerman, Onno; Aleksa, Alena; Alffenaar, Jan Willem; Al-Marzouqi, Nada Hassan; Arias Guillén, Miguel; Belilovski, Evgeny; Bernal, Enrique; Boeree, Martin J.; Borisov, Sergey; Bruchfeld, Judith; Cadiñanos Loidi, Julen; Cai, Qingshan; et al. (Elsevier Science, 2019)
The World Health Organization launched a global initiative, known as aDSM (active TB drug safety monitoring and management) to better describe the safety profile of new treatment regimens for drug-resistant tuberculosis (TB) in real-world settings. However, comprehensive surveillance is difficult to implement in several countries.The aim of the aDSM project is to demonstrate the feasibility of implementing national aDSM registers and to describe the type and the frequency of adverse events (AEs) associated with exposure to the new anti-TB drugs.Following a pilot study carried out in 2016, official involvement of TB reference centres/countries into the project was sought and cases treated with bedaquiline- and/or delamanid-containing regimens were consecutively recruited. AEs were prospectively collected ensuring potential attribution of the AE to a specific drug based on its known safety profile.A total of 309 cases were fully reported from 41 centres in 27 countries (65% males; 268 treated with bedaquiline, 20 with delamanid, and 21 with both drugs) out of an estimated 781 cases the participating countries had committed to report by the first quarter of 2019. Keywords: Tuberculosis, MDR-TB, Adverse events, Monitoring, Delamanid, Bedaquiline